Future time perspective, positive emotions and student engagement: a longitudinal study. Issue 7 (2nd July 2020) - Denovan, Andrew; Dagnall, Neil; Macaskill, Ann; Papageorgiou, Kostas
ABSTRACT: Student engagement is a key prognosticator of success, retention and perseverance in higher education. This study used structural equation modelling to evaluate a gain cycle of future time perspective (FTP), positive emotion and student engagement, derived from the broaden-and-build theory (BBT). A further objective was to examine changes within study variables over time. Participants were 217 UK undergraduates sampled at the beginning of the academic year, and the start of the second term. Analysis revealed that levels of positive emotion and engagement decreased, whereas FTP increased. At both time points, FTP predicted higher engagement, and engagement predicted greater positive emotion. Additionally, Time 1 positive emotion led to increased Time 2 FTP, engagement and positive emotion. This outcome was congruent with the 'build' hypothesis of BBT, suggesting that positive emotions enable the development of psychological resources. Relatedly, interventions designed to enhance FTP and positive emotion can facilitate student engagement and retention.